Surgical interventions for high grade vulval intraepithelial neoplasia - Kaushik, Sonali (2011)
BACKGROUND: Vulval intraepithelial neoplasia (VIN) is a pre-malignant condition of the vulval skin. This uncommon chronic skin condition of the vulva is associated with a high risk of recurrence and the potential to progress to vulval cancer. The condition is complicated by its’ multicentric and multifocal nature. The incidence of this condition appears to be rising particularly in the younger age group. There is a lack of consensus on the optimal surgical treatment method. However, the rationale for surgical treatment of VIN has been to treat symptoms and exclude underlying malignancy with the continued aim of preservation of vulval anatomy and function. Repeated treatments affect local cosmesis and cause psychosexual morbidity thus impacting on the patients’ quality of life. OBJECTIVES: To evaluate the effectiveness and safety of surgical interventions for high grade VIN. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), Issue 3, 2010, Cochrane Gynaecological Cancer Group Trials Register, MEDLINE and EMBASE up to September 2010. We also searched registers of clinical trials, abstracts of scientific meetings, reference lists of included studies and contacted experts in the field. SELECTION CRITERIA: Randomised controlled trials (RCTs) that compared surgical interventions, in adult women diagnosed with high grade vulval intraepithelial neoplasia. DATA COLLECTION AND ANALYSIS: Two review authors independently abstracted data and assessed risk of bias. MAIN RESULTS: We found only one RCT which included 30 women that met our inclusion criteria and this trial reported data on carbon dioxide laser (CO(2) laser) versus ultrasonic surgical aspiration (USA). There was no statistically significant difference in the risk of disease recurrence after one year follow-up, pain, presence of scarring, dysuria or burning, adhesions, infection, abnormal discharge and eschar between women who received CO(2) laser and those who received USA. The trial lacked statistical power due to the small number of women in each group and the low number of observed events, but was at low risk of bias. AUTHORS’ CONCLUSIONS: The included trial lacked statistical power due to the small number of women in each group and the low number of observed events. Therefore in the absence of reliable evidence regarding the effectiveness and safety of the two surgical techniques for the management of vulval intraepithelial neoplasia precludes any definitive guidance or recommendations for clinical practice.